The putative protective role of hepatitis B virus (HBV) infection from autoimmune disorders (2008)
Background: The etiology of autoimmune diseases is not fully clarified and the mechanisms underlying their initiation and progression are still obscure. It is becoming clear that in a genetic susceptible individual an environmental trigger such as infectious agent in general and viruses in particular could initiate the development of an autoimmune disease. Hepatitis B virus (HBV) is notorious in its association with diverse autoimmune diseases. Therefore, we aimed to determine the presence of hepatitis B core antibody (HBcAb), a seromarker for past or present infection with HBV, in a large number of sera collected from patients with different autoimmune diseases. Methods: A cohort of 675 sera samples of 5 different autoimmune diseases and healthy donors were screened for evidence of a prior infection with HBV. All samples were tested for hepatitis B core antibody (IgG) using the Monolisa anti-HBc PLUS commercial kit (Bio-Rad, Hercules, San Francisco, USA). Results: Lower percentage of HBcAb was found in sera of the autoimmune diseases when compared to normal controls. Fifteen (10.7%) from 140 normal controls were found positive for the presence of HBcAb. Two (2%) out of 98 multiple sclerosis (MS) sera were positive for the presence of HBcAb (OR: 0.17, 95%CI: 0.03-0.77, p = 0.01), 3 (2.5%) out of 117 systemic lupus erythematosus (SLE) sera (OR: 0.2, 95%CI: 0.06-0.77, p = 0.01), 4 (4.5%) out of 89 type 1 diabetes (T1D), 5 (6.1%) from 82 Sjogren's syndrome (SS) sera and 12 (8%) from 149 rheumatoid arthritis (RA) sera were positive for the presence of HBcAb. Conclusions: Our data divulge an unexpected low percentage of antibodies to HBcAg in patients with SLE, MS and T1D in comparison to healthy matched donors. This finding may raise a protective role to HBV in some autoimmune diseases i.e. hygiene theory. © 2008 Elsevier B.V. All rights reserved.